Assessment of the Impact of Bowel Preparation Quality on Adenoma Detection Rate in Screening Colonoscopy: A Multicenter Study (Indus Journal of Bioscience Research, 2025)
Introduction: Colonoscopy remains the gold standard for colorectal cancer screening, with the adenoma detection rate (ADR) being a key indicator of the quality of the procedure. Bowel preparation is crucial in ensuring an optimal view of the colon and maximizing the detection of adenomas. Objective: To assess the impact of bowel preparation quality on the adenoma detection rate during screening colonoscopy and provide insights into the necessary quality standards for optimal screening results. Methodology: A cross-sectional study was conducted at This study was conducted at Timergara Teaching Hospital Dir Lower, Timergara, From 2022 to 2023. A total of 220 patients undergoing screening colonoscopy were included. Data on bowel preparation quality, ADR, patient demographics, and other relevant factors were collected. Bowel preparation quality was categorized as excellent, adequate, or poor, and ADR was determined based on the presence of adenomas detected during the procedure. Statistical analysis was performed to evaluate the correlation between preparation quality and ADR. Results: The study found a strong correlation between bowel preparation quality and adenoma detection rate. Patients with excellent bowel preparation had a significantly higher ADR compared to those with poor preparation. Inadequate bowel preparation was associated with missed adenomas, especially in the proximal colon. Conclusion: Improving bowel preparation quality is essential for enhancing ADR in screening colonoscopy. Standardized protocols for bowel preparation and patient education should be implemented to ensure optimal outcomes in colorectal cancer screening.